Sustainable land use against the background of a growing wind power industry - Cornelia Ohl; Jan Monsees (Helmholtz-Zentrum für Umweltforschung (UFZ), 2008)
Among the measures discussed as remedies for CO2 emissions reduction renewable energies are prominent as they already provide marketable alternatives to fossil fuels. This holds true especially for wind power, which has multiplied more than twelve-fold on the global scale from 4,800 MW to over 59,000 MW between 1995 and 2005. This is the highest growth rate compared to all other sources of renewable energy. However, is this impressive expansion expected to continue in the near future? Although wind power as a clean technology helps to combat global warming and, as a renewable energy reduces the dependency on the supply of exhaustible fossil fuels, it is not without flaws. There are concerns over adverse effects on human beings, on wildlife and on the landscape. This paper discusses the limits for wind power generation and highlights important conflict areas that may roadblock further expansion of wind power and thus its potential to combat global warming.
Keywords: 330; Windenergie; Bodennutzung; Nachhaltige Entwicklung; Naturschutz; Landschaftspflege; Deutschland